Variation in CDKAL1 gene is associated with therapeutic response to sulphonylureas - Schroner, Zbynek; Javorský, Martin; Halušková, Jana; Klimčáková, Lucia; Babjaková, Eva; Fabianová, Martina; Slabáková, Eva; Kozárová, Miriam; Tkáč, Ivan (Physiological research, 2012)
The aim of the present pilot pharmacogenetic study was to analyse quantitative effects of sulphonylurea treatment in addition to metformin on parameters of glycemic control with respect to CDKAL1 genotypes in patients with type 2 diabetes. Effect of 6-month sulphonylurea therapy on glycemic control according to CDKAL1 genotypes was evaluated in 101 patients with type 2 diabetes who failed to achieve glycemic control on metformin monotherapy. CDKAL1 rs7756992 polymorphism was determined by melting curve analysis of small amplicon following real-time PCR. After sulphonylurea treatment fasting plasma glucose (FPG) levels were significantly different (p=0.045) among three CDKAL1 genotype groups (AA: n=49; AG: n=36; GG: n=16). In a dominant genetic model, carriers of the G-allele (AG+GG, n=52) achieved significantly lower FPG levels in comparison with patients with the AA genotype (6.90±1.08 vs. 7.48±1.12 mmol/l, p=0.013). Consequently, adjusted ΔFPG was significantly higher in the AG+GG compared to the AA group (1.48±1.51 vs. 1.02±1.33 mmol/l, p=0.022). Similar trend was observed for HbA1c levels, but the difference between the genotype groups did not reach the level of statistical significance. Relatively small number of included patients is a limitation of the present study. In conclusion, our results suggest that the magnitude of FPG reduction after 6-month sulphonylurea treatment in patients with type 2 diabetes is related to the variation in CDKAL1.
Keywords: senioři; genotyp; krevní glukóza; Male; Sulfonylurea Compounds; cyklin-dependentní kinasa 5; Genotype; metformin; Middle Aged; mužské pohlaví; Diabetes Mellitus, Type 2; genetická variace; diabetes mellitus 2. typu; Cyclin-Dependent Kinase 5; hypoglykemika; Genetic Variation; Blood Glucose; ženské pohlaví; Humans; lidé středního věku; Female; Aged; Hypoglycemic Agents; Metformin; lidé; sulfonylmočovinové sloučeniny